An integrated computational and experimental study uncovers FUT9 as a metabolic driver of colorectal cancer. Issue 12 (1st December 2017) - Auslander, Noam; Cunningham, Chelsea E; Toosi, Behzad M; McEwen, Emily J; Yizhak, Keren; Vizeacoumar, Frederick S; Parameswaran, Sreejit; Gonen, Nir; Freywald, Tanya; Bhanumathy, Kalpana K; Freywald, Andrew; Vizeacoumar, Franco J; et al.
Abstract: Metabolic alterations play an important role in cancer and yet, few metabolic cancer driver genes are known. Here we perform a combined genomic and metabolic modeling analysis searching for metabolic drivers of colorectal cancer. Our analysis predicts FUT9, which catalyzes the biosynthesis of Ley glycolipids, as a driver of advanced‐stage colon cancer. Experimental testing reveals FUT9's complex dual role; while its knockdown enhances proliferation and migration in monolayers, it suppresses colon cancer cells expansion in tumorspheres and inhibits tumor development in a mouse xenograft models. These results suggest that FUT9's inhibition may attenuate tumor‐initiating cells (TICs) that are known to dominate tumorspheres and early tumor growth, but promote bulk tumor cells. In agreement, we find that FUT9 silencing decreases the expression of the colorectal cancer TIC marker CD44 and the level of the OCT4 transcription factor, which is known to support cancer stemness. Beyond its current application, this work presents a novel genomic and metabolic modeling computational approach that can facilitate the systematic discovery of metabolic driver genes in other types of cancer. Synopsis: A combined computational and experimental analysis reveals FUT9 as a new, context‐dependent driver of colon cancer. FUT9 expression is required in tumor initiating cells while its loss favors bulk tumor growth and supports tumor aggressiveness. A combined genomic and metabolic modeling analysis is performed to identify metabolic drivers of colorectal cancer. FUT9, which catalyzes the biosynthesis of Ley glycolipids in the Golgi compartment, emerges as a driver of advanced stage colon cancer. FUT9 activity has different effects on tumor initiating cells vs. bulk tumor cells, supporting the former but attenuating the latter. The presented combined computational and experimental approach can be applied for the systematic discovery of metabolic driver genes in other cancer types. Abstract : A combined computational and experimental analysis reveals FUT9 as a new, context‐dependent driver of colon cancer. FUT9 expression is required in tumor initiating cells while its loss favors bulk tumor growth and supports tumor aggressiveness.